Peran Kepala Desa dalam Meningkatkan Pelayanan Publik Masyarakat di Desa Selebung Ketangga Kecamatan Keruak: The Role of the Village Head in Improving Public Services to the Community in Selebung Ketangga Village, Keruak District - Samsul Hadi; Jumatriadi; Dedi Susilo Prayoga; Riduan Miarnata; Ricky Lucky Hidayat (Al-Faizi : Jurnal Politik, Hukum dan Bisnis, 2026)
Public services are a key component of village governance, geared toward meeting the needs and interests of the community. The village head plays a crucial role in establishing policies and implementing public services at the village level. This study aims to describe and analyze the role of the village head in improving public services in Selebung Ketangga Village, Keruak District. This study employed a descriptive qualitative approach, with data collection methods including interviews, observation, and documentation. The results indicate that the Selebung Ketangga Village Head plays an active role in improving public services by acting as a motivator, facilitator, and mobilizer. As a motivator, the Village Head encourages active community participation in village government and development activities. In his role as a facilitator, the Village Head facilitates community access to administrative and social services and fosters good communication between the village government and residents. As a mobilizer, the Village Head mobilizes local resources, including youth and the Youth Organization (Karang Taruna), to contribute to village development.